Attitudes toward sexual and reproductive health and rights and their associations with reproductive agency: a population-based cross-sectional study in Ethiopia, Kenya, and Zimbabwe - Karin Båge; Anna Kågesten; Olalekan Uthman; Mariano Salazar; Bi Puranen; Signe Svallfors; Anna Mia Ekström; Helena Litorp (Sexual and Reproductive Health Matters)
We investigated the association between values and attitudes toward sexual and reproductive health and rights (SRHR) and gender equality, with reproductive agency in Ethiopia, Kenya, and Zimbabwe. Using 2020-21 World Values Survey (WVS) data (n = 3096), we utilised the SRHR Support Index including five subindices to gauge SRHR attitudes, the WVS Equality Index for gender equality values, and the perceived level of freedom of choice and control over whether, when, and how many children to have as a proxy for reproductive agency. Descriptive statistics, bivariate, and multivariable logistic regressions were used to analyse how values and attitudes differed between respondents of high vs low reproductive agency using the median as cut-off, stratified by country and sex. Country, education, subjective social class, and religion were associated with reproductive agency. Adjusted analyses indicated associations between supportive values and attitudes towards equitable masculinity norms, SRHR interventions and gender equality, with high reproductive agency. Associations varied more between countries than by sex. Findings suggest an association between SRHR and gender equality values and attitudes and the level of reproductive agency, and underscore the importance of addressing values and attitudes in context-specific interventions. Measures of SRHR progress should be critically reviewed and complemented with self-assessed – as opposed to researcher-ascribed – items to support the successful implementation of global SRHR agendas.